Did cuts in state aid during the great recession lead to changes in local property taxes? - Rajashri Chakrabarti; Max Livingston; Joydeep Roy (Federal Reserve Bank of New York, 2013)
During the Great Recession and its aftermath, state and local governments' revenue streams dried up due to diminished taxes. Budget cuts affected many aspects of government; in this paper, we investigate whether (and how) local school districts modified their funding and taxing decisions in response to changes in state aid in the post-recession period. Using detailed district-level panel data from New York and a fixed effects as well as an instrumental variables strategy, we find strong evidence that school districts did indeed respond to state aid cuts in the post-recession period by countering the cuts. In comparison with the pre-recession period, a unit decrease in state aid was associated with a relative increase in local funding per pupil. To further probe the school district role, we explore whether the property tax rate, which districts set each year in response to budgetary needs, also responded to state aid cuts. Indeed, we find that relative to the pre-recession period, the post-recession period was characterized by a strong negative relationship between the property tax rate and state aid per pupil. In other words, after the recession a unit decrease in state aid was associated with a relative increase in the property tax rate in the post-recession period (in comparison with the pre-recession period).
Keywords: H40; I21; I28; 330; school finance; Great Recession